Locked up while locked down: prisoners’ experiences of the Covid-19 pandemic - Suhomlinova, Olga (The British journal of criminology, 2022)
Worldwide, the COVID-19 pandemic has had a devastating impact on prisoners. The prison environment and prisoner health put prison populations at a higher risk of contracting COVID-19. As a result, prison systems have adopted mitigation strategies to reduce the transmission of the virus into and within prisons. These strategies, however, have had an unintended impact on prisoners and their living conditions. In this article, we explore prisoners’ lived experiences of the pandemic in English and Welsh prisons, captured through correspondence with prisoners throughout 12 months of regime restrictions, from April 2020 to April 2021. Drawing on prisoner narratives, the analysis reveals how the restricted regime has exacerbated the pains of imprisonment and had a detrimental impact on prisoners.